2012
DOI: 10.4049/jimmunol.1102259
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of IL-4 and IL-4Rα Interaction in Adaptive Immunity of Zebrafish: Insight into the Origin of Th2-like Regulatory Mechanism in Ancient Vertebrates

Abstract: The roles of IL-4 and IL-4Rα in Th2-mediated immunity have been well characterized in humans and other mammals. In contrast, few reports have been documented in ancient vertebrates. Several putative IL-4– and IL-4Rα–like molecules were identified recently from a few fish species, providing preliminary insight into the occurrence of Th2-type immunity in teleosts. However, functional determination still is required to address this hypothesis. To this end, these two molecules were characterized functionally in ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 73 publications
0
70
0
Order By: Relevance
“…Motifs important for downstream pathways are also conserved on several receptor subunits, including the conserved STAT5 docking sites (YXXV/L/M) on Il-2rb, Il-4ra, and Il-7ra (87)(88)(89), and a docking site for SHC, which contributes to activation of the PI3K and ERK pathways, on Il-2rb (64) (data not shown). Ligands of the IL-2R family identified in zebrafish include Il-4, Il-15, Il-15-like, and Il-21 (29,90), with potential Il-2 (91-93) and Il-7 ligands (94) characterized in other teleosts, but not Il-9 (95). Therefore, the phenotypes observed following knockdown of il-2rgc.a and jak3 could potentially be due to defective signaling via several cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Motifs important for downstream pathways are also conserved on several receptor subunits, including the conserved STAT5 docking sites (YXXV/L/M) on Il-2rb, Il-4ra, and Il-7ra (87)(88)(89), and a docking site for SHC, which contributes to activation of the PI3K and ERK pathways, on Il-2rb (64) (data not shown). Ligands of the IL-2R family identified in zebrafish include Il-4, Il-15, Il-15-like, and Il-21 (29,90), with potential Il-2 (91-93) and Il-7 ligands (94) characterized in other teleosts, but not Il-9 (95). Therefore, the phenotypes observed following knockdown of il-2rgc.a and jak3 could potentially be due to defective signaling via several cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the phenotypes observed following knockdown of il-2rgc.a and jak3 could potentially be due to defective signaling via several cytokines. Zebrafish Il-4 has been shown to stimulate B cell proliferation and Ab production in adult fish (29), but its role in T cell development has not been determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key Th-1 cytokines IFN-γ and IL-12 were not significantly regulated, whereas IL-4/13A and IL-4/13b-hallmark cytokines of the Th2 pathway-were significantly upor down regulated, respectively, after 72 hpi in both treated groups. At the moment it is not clear if the two paralogous IL4-/13-genes in zebrafish are functionally comparable to their mammalian counterparts, but is has been suggested that IL-4/13Acorrespond to IL-4 in zebrafish [55]. In two recent studies, IL-4/13b gene expression was elevated in zebrafish and carp kidney cell lines exposed to antigens, whereas IL-4/13a expression was unaffected [54] [56].…”
Section: Discussionmentioning
confidence: 99%
“…T lymphocytes in non-specific response would produce interferon that can activate performance macrophages through phagocytosis mechanism in the face of parasites, bacteria, viruses and foreign particles that are considered as an antigen [10]. Whereas, in the specific immune response, cytokines, including IL-4, IL-5 and IL-13 with the Th cells, will activate B lymphocytes and T lymphocytes [11].…”
Section: Introductionmentioning
confidence: 99%